Arabicization: Morphological or Syntactic Phenomenon? - Ahmed, Mahgoub Dafalla; Ahmed, Mahgoub Dafalla; Nugdalla, Majduldin Sayed (Advances in Social Sciences Research Journal, 2017)
The current study explores the nature of Arabicization from the viewpoint of whether it is morphological, syntactic or morpho-syntactic phenomenon. It describes the lexicology of Arabicized words: the structure of words, meaning components and their relations to each other. The study attempts to approach the etymological methods of entry of lexical items into Arabic as with respect to loan words, derivation and generation and their roles in word-formation processes. Additionally, the study tries to investigate whether derivation processes can work with the Arabicized words. It seeks to establish the difference between the original Arabic words and the Arabicized words on the basis of which concept of Arabicization formerly and presently shall be approached. It ultimately seeks to pinpoint the fact pertinent to the efforts exercised to design a linguistic methodology to handle the Arabicized words along the lines of original existing Arabic terms. This is carried out with the aim of adjusting poly-term phenomenon chiefly observed in Arabic in having a number of equivalents for a single concept as corresponding to that of the source language.